The 21st International ACM SIGACCESS Conference on Computers and Accessibility 2019
DOI: 10.1145/3308561.3353780
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Adoption of Mobile Accessibility Features by Older Adults Experiencing Ability Changes

Abstract: To investigate how older adults perceive ability changes (e.g., sensory, physical, cognitive) and how attitudes toward those changes affect perception and adoption of built-in mobile accessibility features (such as those found on Apple iOS and Google Android smartphones and tablets), we conducted an interview study with 14 older adults and six of their family members. Accessibility features were difficult for participants to find and configure, which were issues compounded by a reluctance to use trial-and-erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Poorly designed user interfaces that are difficult to interact with due to the requirement of several factor authentications and inputs, slow and freezing, [ 30 , 36 , 48 ] poor connectivity [ 112 ], and lack of notification system [ 30 ] were identified as barriers to digital engagement among older adults. By contrast, simple login procedures, accessible, customizable and easy access technologies, including large displays, touch screens, high-definition sound and pictures, high-quality outputs and the ability to give printouts to facilitate engagement [ 31 , 38 , 41 , 84 , 85 , 113 , 116 ]. Automated technologies with instant feedback and interactive features; and the ability to track performance were received more favorably [ 55 , 84 , 90 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Poorly designed user interfaces that are difficult to interact with due to the requirement of several factor authentications and inputs, slow and freezing, [ 30 , 36 , 48 ] poor connectivity [ 112 ], and lack of notification system [ 30 ] were identified as barriers to digital engagement among older adults. By contrast, simple login procedures, accessible, customizable and easy access technologies, including large displays, touch screens, high-definition sound and pictures, high-quality outputs and the ability to give printouts to facilitate engagement [ 31 , 38 , 41 , 84 , 85 , 113 , 116 ]. Automated technologies with instant feedback and interactive features; and the ability to track performance were received more favorably [ 55 , 84 , 90 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Error-recovery support such as back function allowed them to recover to the last correct position, where they could safely proceed. While previous work found that older adults are hesitant to conduct trial-and-error due to factors such as lack of encouragement for self-diagnosis [18] and self-perception of changes in abilities [20], our findings provided encouraging evidence that older adults are more willing and confident to use trial-and-error approach if they are well supported with interactive error-recovery mechanism, such as the ones explored in our work, and were assured that errors would not result in severe consequences [3].…”
Section: Discussion 71 Key Takeawaysmentioning
confidence: 99%
“…For example, a lack of knowledge about technologies' capabilities led some participants to avoid them, such as the avoidance of ftness trackers by people who use wheelchairs, even though some systems (such as Apple Watch [2]) have deployed adaptations to support wheelchair users following research on this issue [13]. Similarly, a lack of awareness of existing accessibility functions for mainstream technologies like phones [21,43] and web browsers [9] has been documented in prior studies. The broader socio-technical context of marketing materials, setup instructions, system defaults, and accessibility options for systems may need to be reconsidered in order to ensure that existing solutions are utilized efectively.…”
Section: Discussionmentioning
confidence: 99%